The Effect Of Ease Of Accessibility, Transaction Security, And Product Quality On Purchasing Decisions For Electronic Devices Online In Jabodetabek Case Study: (Tokopedia Users In Millennials) - Mohamad Ridwan; Sutopo, Sutopo (Jurnal Ekonomi, 2024)
In this technological era, the use of e-commerce in purchasing goods makes it very easy for consumers, including electronic purchases. This research aims to analyze the direct influence of the variables ease of access, transaction security, ease of accessibility, transaction security and product quality on online purchasing decisions for electronic devices in Jabodetabek with the research object being the millennial generation. as a research object. The approach used is quantitative with an associative method, where primary data is obtained through distributing questionnaires. The data analysis techniques used include descriptive statistics, descriptive statistics, and Structural Equation Modeling (SEM) analysis using the Partial Least Square (PLS) method, where all data is processed using the SmartPL application. The research results show that Ease of Accessibility (KA) has a P Values ​​value of 0.082, which shows a significant influence on the Purchase Decision of electronic devices (KPN) on Tokopedia. Transaction Security (KT) has a P Values ​​value of 0.057, which indicates a significant influence on purchasing decisions for electronic devices (KPN) on Tokopedia. Product Quality (KP) has a P Values ​​value of 0.077, which indicates a significant influence on purchasing decisions for electronic devices (KPN) on Tokopedia.